Lower cervical trauma an orthopaedician domain - Charan, Rajat (International Journal of Research in Orthopaedics, 2017)
Background: Lower cervical spinal injuries are potentially devastating injuries of the axial skeleton. Many effective procedures are available for degenerative cervical spinal injuries that are unresponsive to conservative management. Our present aimed to observe the outcome for the treatment of different types of spinal injuries based onASIA impairment scale (modified Frankels scoring system) by using different treatment concepts. Methods: This study was conducted at Indira Gandhi institute of medical sciences and Nalanda medical college during the period 2012 – 2015. 14 patients with lower cervical spine injury attended to emergency department were included in the study. All the 14 cases were operated by different surgical procedures based on type of injury. The outcome was measured by using ASIA impairment scale (modified Frankels scoring system). Results: Out of 14 cases, 3 were burst fractures, 4 were unilateral facet dislocations, 5 were bilateral facet dislocations and 2 with distractive extension injury. Cases with burst fractures operated with corpectomy with cage and plate, for unilateral and bilateral dislocations open reduction and Bohlmantriple-wiring and posterior fusion was done and for distraction injury, open reduction and anterior plating was done. Improvement in Frankel scoring system was good in about 3 cases with unilateral dislocations. Overall, neurological recovery was observed in 35% cases. Recovery was much better in Quadriparesis patients. None of the patients had iatrogenic paresis. Conclusions: Satisfactory results and outcome was observed in unilateral facet dislocations after treatment by open reduction and Bohlman triple-wiring and posterior fusion. The outcome in bilateral facet dislocations was poor as they are easily reduced with closed traction methods.